Hydrogen sulphide reduces hyperhomocysteinaemia‐induced endothelial ER stress by sulfhydrating protein disulphide isomerase to attenuate atherosclerosis - Jiang, Shan (J Cell Mol Med, 2021)
Hyperhomocysteinaemia (HHcy)‐impaired endothelial dysfunction including endoplasmic reticulum (ER) stress plays a crucial role in atherogenesis. Hydrogen sulphide (H(2)S), a metabolic production of Hcy and gasotransmitter, exhibits preventing cardiovascular damages induced by HHcy by reducing ER stress, but the underlying mechanism is unclear. Here, we made an atherosclerosis with HHcy mice model by ApoE knockout mice and feeding Pagien diet and drinking L‐methionine water. H(2)S donors NaHS and GYY4137 treatment lowered plaque area and ER stress in this model. Protein disulphide isomerase (PDI), a modulation protein folding key enzyme, was up‐regulated in plaque and reduced by H(2)S treatment. In cultured human aortic endothelial cells, Hcy dose and time dependently elevated PDI expression, but inhibited its activity, and which were rescued by H(2)S. H(2)S and its endogenous generation key enzyme‐cystathionine γ lyase induced a new post‐translational modification‐sulfhydration of PDI. Sulfhydrated PDI enhanced its activity, and two cysteine‐terminal CXXC domain of PDI was identified by site mutation. HHcy lowered PDI sulfhydration association ER stress, and H(2)S rescued it but this effect was blocked by cysteine site mutation. Conclusively, we demonstrated that H(2)S sulfhydrated PDI and enhanced its activity, reducing HHcy‐induced endothelial ER stress to attenuate atherosclerosis development.